Energy-water nexus design and operation towards the sustainable development goals - Wang, X; Van Dam, K; Triantafyllidis, C; Koppelaar, R; Shah, N (Elsevier, 2019)
Urbanization is taking place rapidly, while the planning of energy, water and resource capacities in many cities especially in developing countries is lagging behind. Motivated by the lack of transparent data-driven decision-making support, a systematic methodology to support sustainable development emphasizing the energy-water nexus and multiple resource systems is developed. It serves as an open-source integrated tool to advice the planning, operation and decision-making considering social, environmental and economic sustainability globally. Several applications of the platform are demonstrated based on a sub-Saharan African metropolitan area. The outputs depict energy, water, and other resource demand, supply and transport on multiple spatiotemporal scales, which are used to indicate cost effective and environmentally friendly development strategies. The total Greenhouse Gas (GHG) emissions associated with the nexus are minimized to 0.56 tonnes CO2 equivalent per capita in 2030, resulting to a 51.4% reduction compared with the business-as-usual scenario, while providing sufficient resources to address sustainable development goals.